Innovative Split Cast Post and Core Technique to Restore a Mutilated Mandibular Molar - Karan Amrutlal Gada; V. N. V. Madhav; Sonal Raikar; Mansi Oswal (Journal of International Clinical Dental Research Organization, 2024)
Dental caries is an inevitable event in patients with compromised oral hygiene, leading to hard tissue breakdown and causing severe loss of tooth structure. The mutilated tooth is grossly weakened and badly broken down carious tooth due to the least attention given toward oral health. The conservation approach is always given priority to save this type of tooth rather than proceeding with the extraction of the tooth. Prosthodontic management of this kind of tooth becomes essential to restore the proper form and function for masticatory purposes. The only method to restore this complication is by post and core procedure. The following case report focuses on the way to restore a mutilated mandibular 1st molar with divergent roots with a split cast post and core wherein one cast post with split core is restored in the distal canal and another cast post with core seated in one of the mesial canals in step and ladder pattern.